Development of Heat Treatments for Selective Laser Melting Ti6Al4V Alloy: Effect on Microstructure, Mechanical Properties, and Corrosion Resistance. Issue 8 (3rd June 2020) - Cecchel, Silvia; Ferrario, Davide; Cornacchia, Giovanna; Gelfi, Marcello
Abstract : To evaluate the introduction of selective laser melting (SLM) for serial application, some features directly related to the components safety and performances are to be deeply analyzed. To this purpose, the present article applies three different types of heat treatment on Ti6Al4V as‐received samples produced by SLM: 1) annealing stress relieving, 2) solubilization super‐β transus, and 3) sub‐β transus followed by a tempering. Then, the related microstructures, mechanical resistance, residual stresses, and corrosion resistance are studied. The results identify a set of heat treatment parameters (super‐β transus followed by tempering), which guarantee the required properties. These samples show equiaxial grains composed of α + β phase, good mechanical properties, a high resistance to corrosion, and residual stresses almost null. Finally, this study confirms that Ti6Al4V made by SLM is applied in the transport field. Abstract : The main purpose of the article is to investigate features connected to the application of selective laser melting (SLM) for the weight reduction of automotive components. Thus, different types of heat treatment on Ti6Al4V are developed, and microstructure, mechanical resistance, residual stresses, and corrosion resistance are deeply investigated. The results confirm that the selected heat treatment guarantees the properties required.